1996
DOI: 10.1055/s-2007-994433
|View full text |Cite
|
Sign up to set email alerts
|

Intrapartum Chemoprophylaxis for Group B Streptococcus Infection to Prevent Neonatal Disease: Who Should be Treated?

Abstract: The purpose of this study was to examine the maternal risk factors associated with early onset Group B streptococcus (GBS) sepsis and determine the potential impact of intrapartum chemoprophylaxis using these risk factors. Using a computerized perinatal database, 26,525 deliveries over a five-year period (1989 to 1994) were identified. Neonates with GBS-positive cultures were identified and the neonatal and maternal chart of each case was reviewed. Twenty-six neonates (1 of 1000) had GBS sepsis documented by b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Although having had a previous infant with invasive GBS disease is accepted widely as placing a mother at high risk in subsequent pregnancies, only four instances have been reported in which neonatal GBS infection followed more than one pregnancy in the same mother. [137][138][139] We have seen other instances of this event, so it probably is not as unusual as is suggested by the rarity of reported cases. Women may remain colonized with the same strain of GBS for prolonged periods 140 and may fail to develop protective levels of type-specific serum antibodies despite long-term colonization.…”
Section: Sibling With Gbs Infectionmentioning
confidence: 51%
“…Although having had a previous infant with invasive GBS disease is accepted widely as placing a mother at high risk in subsequent pregnancies, only four instances have been reported in which neonatal GBS infection followed more than one pregnancy in the same mother. [137][138][139] We have seen other instances of this event, so it probably is not as unusual as is suggested by the rarity of reported cases. Women may remain colonized with the same strain of GBS for prolonged periods 140 and may fail to develop protective levels of type-specific serum antibodies despite long-term colonization.…”
Section: Sibling With Gbs Infectionmentioning
confidence: 51%
“…17 However, subsequent studies have shown that only approximately 50% of mothers with infants who developed neonatal disease had identifiable risk factors. [18][19][20] Thus, a clinical risk factor based approach would lead to unnecessary treatment of a large number of women and, more importantly, would fail to prevent around 50% of cases.…”
mentioning
confidence: 99%